Drug Safety Surveillance in China and Other Countries: A Review and Comparison - Du, Wenmin (Value Health, 2008)
OBJECTIVES: Drug safety and postmarketing surveillance have become important public health issues in China. This study reviews the relatively new drug safety surveillance system in China and compares it with the systems in the United States and Europe. METHODS: An extensive literature review was conducted in the following four areas: 1) the organizational structure of the State Food and Drug Administration (SFDA) in China; 2) the development of an adverse drug reaction (ADR) monitoring system in China; 3) regulatory issues related to drug safety in China; and 4) similarities and differences between drug safety surveillance in China and surveillance in the United States and Europe. RESULTS: The SFDA oversees an extensive network of drug safety “watchdogs,” including the China National Center for ADR Monitoring and 32 regional centers throughout China. China's system has faced a number of recent challenges. It has had to respond quickly to the withdrawal of various high-profile drugs like Vioxx (rofecoxib) and Baycol (cerivastatin) from other markets. Together with China's Ministry of Health, the SFDA has faced several unique drug safety events. Three of those events, involving the injectable form of the heartleaf houttuyinia herb (Yu Xing Cao), Armillarisni A injections, and clindamycin glucose infusions (Xinfu), are discussed. The rapid development of drug safety surveillance in China is manifested in extensive organizational structure, development of large databases, and laws and regulations supporting drug safety. The two major laws are the China Drug Administration Law issued in February 2001 and the Regulation for the Administration of ADR Reporting and Monitoring issued in March 2004. The study also discusses and compares recent developments in drug safety surveillance in the United States and the European Union. These developments will most likely have implications for the Chinese system in the near future. CONCLUSIONS: While postmarketing surveillance guidelines are not yet available in China, we fully expect their eventual issuance after adaptation to the particular culture and clinical practices in China.